Leitura recombinativa em pessoas com necessidades educacionais especiais: análise do controle parcial pelas sílabas - ALVES, Keila Regina Sales (2013)
The syllabic restricted control makes the recombinational reading difficult; however it can be reverted by some teaching procedures. This study verified the syllabic control and the effects of teaching procedures. Three special students were taught the dictated words-pictures and dictated words-written words relations, and tested the textual and comprehensive reading of taught and generalized words with syllables recombination. If this reading did not occur, syllabic control probes were applied together with isolated and combined teaching. If the reading occurred, A'B'/A'C'/B'C'/C'B' tests were applied. The three participants demonstrated comprehensive reading of the taught words. Two of them presented the textual reading of these words promptly. The textual and comprehensive reading of the generalized words occurred after the second teaching sequence. The restricted control by one syllable makes the generalized reading by syllabic recombination difficult, but this control can be reverted through some teaching procedures that guarantee the visual and sound discrimination and oral reproduction of the syllables.